Assessment of the Cavitation Models Implemented in OpenFOAM® Under DI-like Conditions. (November 2016) - Cazzoli, Giulio; Falfari, Stefania; Bianchi, Gian Marco; Forte, Claudio; Catellani, Cristian
Abstract: Direct injection engine performance is strictly correlated to the fluid dynamic characteristics of the injection system. Actual DI engines, both Diesel and gasoline, employ injector characterized by high injection pressure that, associated to micro-orifice design, result in cavitation flow conditions inside injector holes. The cavitation has a beneficial effect on the atomization process and a negative one on the physical erosion generated by the vapor bubble collapse. In order to quantify both effects with a numerical approach, the reduced dimension and the complex flow structures reduce the efficacy of an experimental approach, thus the cavitation model used is of primary importance. The present work addresses the validation of the mixture model-based cavitation models that are implemented in OpenFOAM®, with particular focus on the Schnerr and Sauer model, using the experimental results, available in literature, for a two-phase flow in an optically accessible nozzle under diesel-like conditions.